Исследование механизма гелеобразования в гибридных гелях кремнезема с пониженной склонностью к агрегированию - Скородумова, Ольга Борисовна; Лозовской, А. Ю.; Тарахно, Елена Витальевна; Гонтар, Татьяна Борисовна (Национальный технический университет "Харьковский политехнический институт", 2014)
Исследовано влияние основных технологических параметров получения на гидрофобизацию поверхности частиц гибридных гелей SiO₂ и склонность их к агрегированию. Изучено влияние технологических особенностей проведения золь-гель перехода на механизм гелеобразования в гибридных гелях системы метилтриэтоксисилан–тетраэтоксисилан, в условиях переменного рН. Установлено, что для получения тонких порошков в высокой текучестью и низкой склонностью к агрегированию необходимо проводить коагуляцию готового гидролизата МТЭОС/ТЭОС= 2/1 при рН 9 через 0,5 ч. после приготовления.

The influence of main technological parameters of receipt on the hydrophobization of particles surfaces of hybrid SiO₂ gels and their tendency to aggregate has been studied. Research used the gels methyltriethoxysilane and tetraethoxysilane at a ratio MTEOS/TEOS = 2/1 - 4/1 received by joint hydrolysis in acidic aqueous-alcoholicmedium under variable pH. Using infrared spectroscopy, it has been studied the impact of technological characteristics (ratio MTEOS/TEOS, pH and coagulation time) Sol-gel transition on the mechanism of gel formation in hybrid gels system methyltriethoxysilane - tetraethoxysilane. It is established that the presence of methyltriethoxysilane in the initial mixture does not accelerate the hydrolysis of tetraethoxysilane, but has a significant impact on the process of polycondensation products of hydrolysis methyltriethoxysilane and intermediates of the hydrolysis of tetraethoxysilane and the degree of homogeneity of the gel. Uniform distribution of the hydrophobic CH₃ groups between the surface silanol groups prevents the formation of aggregates in the powder silica gel, increases the fluidity of powders and provides high values of their adsorption activity.
Investigation of the mechanism of gelation inhybrid silica gels with reduced propensity for aggregation
Keywords: метилтриэтоксисилан; тетраэтоксисилан; гидролиз; поликонденсация; methyltriethoxysilane; tetraethoxysilane; hydrolysis; polycondensation; mechanism of gelation; tendency to aggregation